Pengaruh Disiplin dan Kepemimpinan Diri dengan Kinerja Pegawai Direktorat Perkapalan dan Kelautan - Bobi satria; Aprizawati Aprizawati; Romadhoni Romadhoni (Alignment:Journal of Administration and Educational Management, 2020)
The purpose of this study was to determine the effect of discipline and self-leadership on the performance of the Directorate of Shipping and Maritime employees. The research method used in this study is a survey with the type of correlational research. The results showed the value of the correlation coefficient between leadership style and employee performance amounted to 0.613, leadership style can contribute to improving employee performance that is 37.5%. Furthermore, the correlation coefficient between work discipline and employee performance is 0.710, meaning that work discipline also contributes high enough to improve employee performance by 50.4%. Furthermore, the results of correlation and multiple regression of leadership style, and work discipline together with employee performance obtained a large correlation coefficient of 0.759 or 57.6%. In conclusion, the three independent variables are leadership style (X1), and work discipline (X2), which are variables that need attention. In other words, that the three independent variables are leadership style (X1), and work discipline (X2) are variables that are effective enough to improve employee performance. Keywords: Discipline, Leadership, Performance, Service